2020
DOI: 10.3390/v12090913
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Serotype 4 Is Responsible for the Outbreak of Dengue in East Java City of Jember, Indonesia

Abstract: Outbreaks of dengue virus (DENV) in Indonesia have been mainly caused by the DENV serotype-1; -2; or -3. The DENV-4 was the least-reported serotype in Indonesia during the last five decades. We recently conducted a molecular epidemiology study of dengue in the Jember regency, East Java province, Indonesia. Dengue is endemic in the region and outbreaks occur annually. We investigated the clinical characteristics and etiology of dengue-like febrile illness in this regency to understand the disease dynamics. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
2
16
0
2
Order By: Relevance
“…Molecular epidemiology has become an indispensable tool in determining routes and sources of infection in human and animal viral infections. Determination and comparison of viral variants, sero- or genotypes, has proven vital, not only in the current coronavirus pandemic but also in allowing us to link the new introduction of serotype 4 to emerging outbreaks of dengue virus in Indonesia, or recognize frozen berries as the source of a multistate outbreak of hepatitis A in Europe [ 28 , 29 , 30 ]. Furthermore, substantial sequence databases have helped tracing chains of (re-)infection of bovine viral diarrhea virus and supported the eradication of this epizootic cattle pathogen in Switzerland and Scotland [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular epidemiology has become an indispensable tool in determining routes and sources of infection in human and animal viral infections. Determination and comparison of viral variants, sero- or genotypes, has proven vital, not only in the current coronavirus pandemic but also in allowing us to link the new introduction of serotype 4 to emerging outbreaks of dengue virus in Indonesia, or recognize frozen berries as the source of a multistate outbreak of hepatitis A in Europe [ 28 , 29 , 30 ]. Furthermore, substantial sequence databases have helped tracing chains of (re-)infection of bovine viral diarrhea virus and supported the eradication of this epizootic cattle pathogen in Switzerland and Scotland [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although having the lowest prevalence, DENV-4 still has the potential to cause severe dengue manifestation (DHF), as reported in a previous study [17]. The dengue outbreak in Jember manifested as milder (DF) disease, with only 26.7% of patients showing DHF manifestation [13]. Nevertheless, the predominance of DENV-4 during the outbreak raised awareness and scientific questions on whether there are virus factors that contributed to this phenomenon.…”
Section: Introductionmentioning
confidence: 84%
“…Serum samples were collected during a DENV surveillance study in Jember, East Java, from May 2019 to March 2020, which revealed the predominance of DENV-4 [13]. The use of human serum samples in the study was granted ethical approval from the Research Ethics Committee of the Faculty of Medicine Universitas Airlangga, Surabaya, Indonesia (Ethical Approval No.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The DENV-4 was the least-reported serotype in Indonesia during the last five decades. 3 In 2013, the Ministry of Health of Indonesia (MoHI) reported 112,511 cases (dengue Incidence Rate (IR) of 41.25 per 100,000 population) and 871 deaths corresponding to a Case Fatality Rate (CFR) of 0.7%. 4 West Java is home to about 20% of Indonesia's total population, making it one of the most densely populated provinces in the country.…”
Section: Introductionmentioning
confidence: 99%